Non-Gaussian fingerprints of self-interacting curvaton - Enqvist, Kari; Nurmi, Sami; Taanila, Olli; Takahashi, Tomo (Journal of cosmology and astroparticle physics, 2010)
We investigate non-Gaussianities in self-interacting curvaton models treating both renormalizable and non-renormalizable polynomial interactions. We scan the parameter space systematically and compute numerically the non-linearity parameters fNL and gNL. We find that even in the interaction dominated regime there are large regions consistent with current observable bounds. Whenever the interactions dominate, we discover significant deviations from the relations fNL ∼ rdec−1 and gNL ∼ rdec−1 valid for quadratic curvaton potentials, where rdec measures the curvaton contribution to the total energy density at the time of its decay. Even if rdec ≪ 1, there always exists regions with fNL ∼ 0 since the sign of fNL oscillates as a function of the parameters. While gNL can also change sign, typically gNL is non-zero in the low-fNL regions. Hence, for some parameters the non-Gaussian statistics is dominated by gNL rather than by fNL. Due to self-interactions, both the relative signs of fNL and gNL and the functional relation between them is typically modified from the quadratic case, offering a possible experimental test of the curvaton interactions.